Psychological coping skills in female senior volleyball players - Milavic, B.; Milic, M.; Grgantov, Z.; Felja, I.; Dugonjic, B. (World Congress of Performance Analysis of Sport XII, 2018)
To determine the differences related to age and player position in psychological coping skills, 70 female senior players, whose mean age was 20.60±2.90 years, filled out the Athletic Coping Skills Inventory (ACSI-28; Smith et al., 1995). Female senior volleyball players are characterized by low level of Freedom from worry (2.82), moderate level of Peaking under pressure (3.21), Concentration (3.22) and Coping with adversity (3.42), and somewhat higher level of Coachablllty (3.89) and Confidence & Motivation (3.82). Among the 7 measures of the questionnaire, significant difference related to age was determined only in the Freedom from worry variable (F=3.09; p=.047), as the eldest players had significantly higher values in this variable in relation to the other two age groups. The experience of playing at senior level contributes to better control of state anxiety of players. There were no statistically significant positional differences determined in psychological coping skills. The obtained results suggest that psychological coping skills do not cause positional differences between female senior volleyball players as some other dimensions of anthropological status do (e.g., anthropometric characteristics, motor skills, technical and tactical skills, etc). By dividing players into three groups (types) according to their level of psychological coping skills, significant differences are determined between groups of senior players in all the measured variables. It would be justified to assume that psychological skills of players of one group (type 3) may have a great negative effect on their individual sports achievement in a volleyball match.